Magnetite and granular activated carbon improve methanogenesis via different metabolic routes. (1st December 2020) - Lee, Sang-Hoon; Kang, Hyun-Jin; Lim, Tae-Guen; Park, Hee-Deung
Graphical abstract: Highlights: Magnetite resulted in greater enhancement of methanogenesis than GAC. Geobacter species were predominantly observed on GAC. Magnetite was enriched in syntrophic acetate oxidizing bacteria and Geobacter species. Magnetite activated both acetate decarboxylation and CO2 reduction pathways. GAC activated only the CO2 reduction pathway. Abstract: Although supplementation of conductive materials enhances methanogenesis performance by direct interspecies electron transfer (DIET), interplay among different functional microbial groups in response to different conductive materials remains unknown. To investigate the interplay in methanogenesis, acetate-fed batch-type reactors were operated with and without conductive materials (granular activated carbon [GAC] and magnetite), and microbial community analysis and functional gene quantification were performed. Although both GAC and magnetite supplementation improved methanogenic performance, magnetite supplementation was better than GAC supplementation. The reactors supplemented with magnetite showed 31.7% more reduced lag times, 18.3% more enhanced methane production rates, and 4.9% more increased cumulative methane production, compared to those supplemented with GAC. Microbial community analysis demonstrated that DIET-related Geobacter species and their functional genes were remarkably more abundant ( 49.8%) on the GAC surface, while various syntrophic acetate-oxidizing bacteria predominated on magnetite. In the quantitative analysis of functional genes expression, magnetite activated the genes of both acetate decarboxylation and CO2 reduction pathways, while GAC activated only the latter. These results imply that GAC and magnetite differently affect the routes of methanogenesis, subsequently exerting different effects on methanogenesis performance.